Hydrodynamics Concepts and Experiments - Edmar Schulz, Harry (IntechOpen, 2015)
The present book on Hydrodynamics - Concepts and Experiments contains six chapters, each of which devoted to a topic considered interesting to compose this book. Although the tools used in the different chapters are somewhat superposed, a first classification may be presented as: the first two chapters describe numerical models; the third and fourth chapters use experimental tools and results; and the fourth, fifth and sixth chapters present conceptual aspects of fluid dynamics. A more detailed description is furnished in the sequence. The six topics that compose this book may be resumed as: Flow-Structure Interactions, Hydrodynamic Models and Biological processes in Coastal Waters, Useful Cavitation, New Concepts in Hydraulic Jumps, Lagrangian Formulation of Fluid Dynamics, and Small Perturbations in Viscous Fluids.